2016
DOI: 10.1007/s00436-016-5125-z
|View full text |Cite
|
Sign up to set email alerts
|

Henneguya melini n. sp. (Myxosporea: Myxobolidae), a parasite of Corydoras melini (Teleostei: Siluriformes) in the Amazon region: morphological and ultrastructural aspects

Abstract: A new species of myxozoan, Henneguya melini sp. n. (Myxosporea: Myxobolidae), was described based on morphologic and ultrastructural features. This is a parasite of the ornamental freshwater fish C. melini from the Rio Negro, and it was found in five of 30 (16.7 %) C. melini examined. The parasite was found in the gill filaments, and the plasmodia had form of round to ellipsoid, with mature and immature spores inside them. The average spore body was 15.5 ± 0.2 μm in length, 4.7 ± 0.1 μm in width, and the tail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Nonetheless, our observations seem to be the first study reporting the natural occurrence of EAg in fish infected by a myxosporean species. Despite the many studies reporting parasitosis in myxosporean species in other Brazilian fish hosts (Azevedo et al, 2014;Casal et al, 2019;Eiras & Adriano, 2012;Mathews et al, 2016;Rocha et al, 2014), none of these have reported the occurrence of hemagglutination, as a consequence of infection. Moreover, several of the abovementioned studies used LM and molecular procedures and may have missed changes that are only detectable via TEM.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our observations seem to be the first study reporting the natural occurrence of EAg in fish infected by a myxosporean species. Despite the many studies reporting parasitosis in myxosporean species in other Brazilian fish hosts (Azevedo et al, 2014;Casal et al, 2019;Eiras & Adriano, 2012;Mathews et al, 2016;Rocha et al, 2014), none of these have reported the occurrence of hemagglutination, as a consequence of infection. Moreover, several of the abovementioned studies used LM and molecular procedures and may have missed changes that are only detectable via TEM.…”
Section: Discussionmentioning
confidence: 99%
“…Del género Henneguya Thélohan, 1892 podemos afirmar que es el segundo más grande dentro de los Myxosporea, con alrededor de 190 especies descritas a nivel mundial (Eiras & Adriano, 2012) que se caracterizan por ser predominantemente histozoicas, es decir, que son capaces de ocasionar considerables cambios patológicos como la destrucción de filamentos branquiales y ocasionar fallo respiratorio en el huésped (Lom & Dyková, 1992;Morsy et al, 2012;Mathews et al, 2016). Por su parte, los Ceratomyxa Thélohan, 1892 son ampliamente conocidos como parásitos de peces de aguas marinas y salobres; sin embargo, estudios recientes han revelado una creciente diversidad de especies de Ceratomyxa en las vesículas biliares de peces de agua dulce sudamericanos (Zatti et al, 2017;Zatti et al, 2018;Ferreira et al, 2021;Zatti et al, 2022;Araújo et al, 2022).…”
Section: Myxozoaunclassified
“…The species of the genus Henneguya are predominantly histozoic, can infect various organs, and can cause considerable pathological changes (Dyková & Lom, 1978;Molnár, 1998;Pote et al, 2000;Adriano et al, 2005;Naldoni et al, 2009;Barassa et al, 2012;Morsy et al, 2012;Mathews et al, 2016). When they infect the gills, they can cause filament destruction and respiratory failure (Lom & Dyková, 1992).…”
Section: Introductionmentioning
confidence: 99%